Electronic health (eHealth) interventions for weight management among racial/ethnic minority adults: a systematic review. (October 2014) - Bennett, G. G.; Steinberg, D. M.; Stoute, C.; Lanpher, M.; Lane, I.; Askew, S.; Foley, P. B.; Baskin, M. L.
Summary: Electronic health (eHealth) interventions have demonstrated efficacy for weight management. However, little is known about their efficacy among racial/ethnic minority populations, in whom there is a disproportionate prevalence of obesity. This systematic review evaluated the efficacy of eHealth weight management interventions among overweight and obese racial/ethnic minority adults. We required that trial samples be comprised of at least 50% racial/ethnic minorities or report outcomes by race/ethnicity. We searched five electronic databases for trials conducted through June 2012. Six papers met our eligibility criteria. These studies provide suggestive evidence that eHealth interventions can produce low magnitude, short‐term weight loss among racial/ethnic minorities. Trials were methodologically sound, with high retention and participant engagement. There was no evidence detailing the efficacy of mobile health approaches, although this area is promising given high utilization rates of mobile devices among racial/ethnic minorities. More evidence, particularly from longer‐term trials, is necessary to demonstrate that eHealth intervention approaches can produce clinically meaningful (≥5% of initial body weight) weight loss among racial/ethnic minority populations.